قضایا أسلوبیة بین الموروث العربي والمناھج الغربیة الحدیثة - أ.د. حسن مندیل حسن العكیلي (College of Education for Women, 2019)
Find addresses some issues of contemporary stylistic contemporary Arab scholars, and tries to answer. Issue: stylistic roots in the rhetorical Arab heritage. And the issue of reverse between old and contemporary. And proposes a new stylistic take into account the specificity of the Islamic and Arabic text is consistent with the application and analysis.